HIA in Switzerland: considerations concerning the experience of the Cantons of Geneva, Jura and Ticino (Italian Journal of Public Health, 2007)
This article is intended to be an initial report on the experiences gained while using HIA. Although it is provisional and pragmatic, it ought to provide useful elements for comparison with other territorial situations, both Swiss and foreign. The large differences between the three cantonal political-institutional contexts probably explain the profound differences in the way that HIA processes were introduced in each canton. Nevertheless, the article - through the concept of institutionalization - seeks to identify supracantonal elements. Finally, by presenting HIA implementation methods in different Cantons, it endeavours to demonstrate the existence of a common matrix in the Swiss context beyond the differences arising from the actual political-institutional situations linked to them.
Keywords: Local HIA institutionalization; HIA approach; HIA appraisal; assessment tools; Health Policy